The Effect of OHS Procedures and Worker Competence on Occupational Safety and Health with Worker Communication as a Mediator at Public Company (PERUM) Jasa Tirta II - Prastono Wijayanto (Return : Study of Management, Economic and Bussines, 2025)
Occupational safety and health (OHS) is crucial for ensuring a safe and healthy workplace, reducing work-related accidents, and enhancing productivity. This study aims to analyze the effect of OHS Procedures and Worker Competence on Occupational Safety and Health (OHS) with Worker Communication as a mediator at Public Company (PERUM) Jasa Tirta II. The approach used in this research is quantitative with a survey method, which aims to test hypotheses through numerical data analyzed statistically. The population in this study were all employees at PERUM Jasa Tirta II, with sampling techniques using simple random sampling. The number of samples used was 95 employees, which was determined using the Slovin formula with an error rate of 5%. The results showed that OHS procedures and worker competence had a significant effect on occupational safety and health. In addition, worker communication acts as a mediator that affects the relationship between OHS procedures and worker competence with occupational safety and health. The findings confirm that proper implementation of OHS procedures, improvement of worker competencies, and effective communication between workers can improve work safety in the company. This study makes an important contribution to efforts to improve occupational safety and health through an approach that involves procedures, worker skills and effective communication.